Archaeological human remains : global perspectives - Lozada, Maria Cecilia; O'Donnabhain, Barra (SpringerBriefs in Archaeology, 2014)
This volume addresses the directions that studies of archaeological human remains have taken in a number of different countries, where attitudes range from widespread support to prohibition. Overlooked in many previous publications, this diversity in attitudes is examined through a variety of lenses, including academic origins, national identities, supporting institutions, archaeological context, and globalization.   The volume situates this diversity of attitudes by examining past and current tendencies in studies of archaeologically-retrieved human remains across a range of geopolitical settings.  In a context where methodological approaches have been increasingly standardized in recent decades, the volume poses the question if this standardization has led to a convergence in approaches to archaeological human remains or if significant differences remain between practitioners in different countries. The volume also explores the future trajectories of the study of skeletal remains in the different jurisdictions under scrutiny.